(untitled) (Praxis Educativa, 2025)
The article delves into the analysis of the foundations and arguments present in educational regulations and policies that promote the creation of spaces for student participation, especially at the primary level, from the last democratic restoration in 1983 to the present in the Autonomous City of Buenos Aires. The research adopts a historical-ethnographic approach in education and includes a variety of documentary sources in its analysis, including laws, regulations, and state decrees, as well as handwritten documents produced by teachers involved in participatory experiences. The paper examines the historical question of how participatory experiences shifted from being considered dangerous to becoming possible and desirable, fundamentally exploring the reasons behind this acceptance, hypothesizing it as a consequence of their progressive depoliticization.